2012
DOI: 10.1155/2012/692348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of IL10 (G1082A) and TNFα (G308A) Polymorphisms on the Survival of Pediatric Patients with ALL

Abstract: Interleukin 10 (IL10) is a pleiotropic cytokine that stimulates various hematopoietic cells. The tumor necrosis factor alpha (TNFα) is a cytokine that may influence the transcriptional activity induced by glucocorticoids. This study examined the impact of TNFα (G308A) and IL10 (G1082A) polymorphisms at promoter regions in relation to the overall survival of 105 children (0 ≤ 18 years) with acute lymphoblastic leukemia (ALL) for a period of 126 months, treated according to the protocol GBTLI99. The G1082A and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…For IL10, disease‐specific distribution differences have already been described in leukaemia. Comparable to our results, in acute myeloic leukaemia (AML) differences referred of the IL10 promoter gene polymorphism at position −592 and −819 and in ALL at position −1082 have been described . In our cohort, we investigated these three single nucleotide polymorphisms in the promoter of the IL10 gene (−1082, −819 and −592) and showed that the IL10 high‐producer haplotype GCC/GCC was less frequent in ALL patients than in healthy controls .…”
Section: Discussionsupporting
confidence: 79%
“…For IL10, disease‐specific distribution differences have already been described in leukaemia. Comparable to our results, in acute myeloic leukaemia (AML) differences referred of the IL10 promoter gene polymorphism at position −592 and −819 and in ALL at position −1082 have been described . In our cohort, we investigated these three single nucleotide polymorphisms in the promoter of the IL10 gene (−1082, −819 and −592) and showed that the IL10 high‐producer haplotype GCC/GCC was less frequent in ALL patients than in healthy controls .…”
Section: Discussionsupporting
confidence: 79%
“…This finding was also suggested in the study of de Deus et al [36] who showed that IL-10 GG genotype might have a lower risk for prednisone poor response in childhood acute lymphoblastic leukemia.…”
Section: Discussionsupporting
confidence: 76%
“…It is known that rs1800896 polymorphism, within the IL-10 gene promoter region, might influence IL-10 expression and plasma levels [37,38]. It was described that G-allele carrier patients have a better response to ALL treatment which includes glucocorticoids, leading to a better outcome [39,40] A C C E P T E D M A N U S C R I P T…”
Section: Accepted Manuscriptmentioning
confidence: 99%